ARTICULATION OF THE JAVANESE ISLAMIC MYTHIC IDEOLOGY IN THE KRUCIL KEDIRI PUPPETS - Irawanto, Rudi; Anom Kumbara, A.A. Ngurah; Suarka, I Nyoman; Darmana, I Ketut (E-Journal of Cultural Studies; Vol 15 No 1 (2022): Volume 15, Number 1, February 2022DO - 10.24843/cs.2022.v15.i01.p01, 2022)
The Cipto Manunggal Kebatinan Community is a mystical community that has developed in the Kediri area of ??East Java, which strengthens its ideological identity through the Krucil puppet art. Krucil is constructed as a performing art from the kebatinan community, which displays the concepts in the kebatinan teachings they profess. The main concepts in kejawen teachings are reconstructed through symbols in the Krucil puppets, so that the core concepts in kejawen teachings have new meanings. This study uses a critical ethnographic approach to dissect the ideological concepts in the wayang Krucil which is used as an ideological representation of the Cipto Manunggal community. The results of this study indicate that there are 3 main aspects in Cipto manunggal's kebatinan teachings that acquire new meanings, Keywords: ideology, Javanese Islam, wayang Krucil